초탄성 형상기억합금을 활용한 자동복원 가새 프레임 구조물의 내진성능 평가 - 비선형 동적해석 - 반우현; 허종완; 주영훈; Ban, Woo-Hyun; Hu, Jong-Wan; Ju, Young-Hun (대한토목학회논문집, 2020)
Korea was recognized as a relatively safe area for earthquake. However, due to considerable damage to facilities caused by the earthquake in Gyeongju and Pohang, interest in the maintenance and repair of structures is increasing. So interest in vibration damping technology applicable to existing structures is also increasing. However, vibration damping technology has a problem in that its usability is reduced due to damage of the damping device when a strong earthquake occurs. Recently, in order to solve such a problem, study is being conducted to apply a superelastic shape memory alloys (SSMA) capable of recentering bracing. Therefore, in this study, nonlinear dynamic analysis is performed to evaluate the seismic performance of the buckling-restrained braced frame (BRBF) applied SSMA to bracing. 우리나라는 비교적 지진에 대해 안전한 지역으로 인식되고 있었다. 그러나 최근 경주와 포항에서 발생한 지진으로 인한 시설물에 상당한 피해가 발생함에 따라 이미 건축된 구조물의 유지, 보수에 관한 관심이 높아지고 있다. 따라서 기존 구조물에 적용 가능한 제진기술에 대한 관심 또한 높아지고 있다. 그러나 제진기술은 강한 지반 운동으로 인한 장치의 손상으로 인하여 성능 저하의 문제점이 있다. 최근 이러한 문제를 해결하기 위해, 가새 부재에 응력을 제거함으로써 자동복원이 가능한 초탄성 형상기억합금을 적용하는 연구가 이뤄지고 있다. 따라서 본 연구에서는 초탄성 형상기억합금을 적용한 비좌굴 가새 부재를 활용하여 자동복원 프레임 구조물을 구성하고 비선형 동적 해석을 통하여 초탄성 형상기억합금의 재료적 우수성과 구조물의 내진성능을 평가 및 검증하였다.